EARTHWORM ACTIVITY IN FOREST AND SAVANNA SOILS NEAR BOA VISTA, RORAIMA, BRAZIL - GUERRA,Rafael Torquemada (1994)
From May to December, 1992 we studied the earthworm activity, as part of the ECOFIT Program at Surrão ( 30km from Boa Vista), verifying the duration of the activity and quantifying it through the casts deposited on the soil surface. Three transects were stablished: a 100m long in the savanna, a 40m in the transitional area and 100m long in the forest. Specimens were collected monthly along the transects according to the method proposed by TSBF and the casts were collected from the squares previously placed on the transects. Two earthworm species were found in the three areas: Pontoscolex roraìmensis and Pontoscolex corethrurus. The first species depositing its casts on the soil surface. Rainy season wich usually occurs from April to August, determined the duration of activity for the two species (however, 1992 was atypical in that rainy season, only started in May). P. roraìmensis produced casts in the three areas from May to August followed by aestivation. In the savanna, P. corethrurus started aestivation in the same period as P. roraìmensis but remained active until November in the two other areas. P. roraìmensiswas found up 50m from the forest border, being associated to the presence of Curatella americana and Byrsonima sp, two typical savanna bushes.